Design of Auto-roll Supporting Device in the Model of Trans-super-sonic Wind Tunnel - Jiang Minghua; Ye Cheng; Fu Bo (Jixie chuandong)
The roll-angle of test model often needs to be changed automatically in wind tunnel,and then a roll supporting system is needed. Considering that the model of trans-super-sonic wind tunnel bears impulsive loads,and its supporting device profile is defined strictly,a new type of auto-roll supporting device is proposed. A servo-motor and a harmonic reducer,whose dimensions meet the size requirements of the roll supporting device,are chosen as the drive source and the high-speed transmission mechanism respectively. At the same time,a electro-magnetic brake is used to lock turning model. The planetary gear train which can hold and drive the rotating model is chosen as the last stage link. The structure and suitable machining process of the planetary gears train are analyzed and designed. Calculation results show that the shell and solar gear have enough mechanical strength. The running and loading experiments are performed and the results show the roll supporting device with control system can be used as test device of trans-super-sonic wind tunnel.